Comparison of Two Different Vinblastine Dosages for Treatment of Cutaneous Mast Cell Tumor in Dogs - Kluthcovsky, Lucas Cavalli; Firmo, Bruna Fernanda; Cassino, Pedro Carvalho; De Nardi, Andrigo Barboza; Castro, Jorge Luiz Costa; Halila, Renata Luiza; Engracia Filho, Jair Rodini (Acta Scientiae Veterinariae, 2020)
Background: Mast cell tumors (MCT) are among the most common malignant cutaneous neoplasm in dogs with variable biologic behavior and remain a therapeutic challenge in high-grade cases. Surgery remains the primary treatment for canine MCT; however, chemotherapy and radiation therapy are commonly used to treat aggressive cases. The combination of vinblastine (VBL) at a dose of 2 mg/m² and prednisone is the classically described protocol for MCT treatment. Studies have shown the safety of higher VBL doses for dogs with MCT, but there is a lack of information regarding dose intensity and outcome as a goal after chemotherapy. This study aimed to evaluate the impact of a higher dose of VBL on MCT treatment outcome. Materials, Methods & Results: This was an observational and comparative study conducted in two different Veterinary Teaching Hospitals. Client-owned dogs with histopathological diagnosis of grade II or III MCT were selected and underwent at least four chemotherapy sessions with VBL and prednisone. The experimental group (EG) consisted of 18 dogs that received a dose of 3 mg/m² VBL treated in one institution. The control group (CG) included 31 dogs that received a dose of 2 mg/m² VBL treated at the other institution. All dogs treated in both groups had a clinical and complete blood count (CBC) evaluation performed previous the start of chemotherapy (T0) and before each weekly treatment (T1, T2, T3, and T4). After treatment, dogs in both groups were followed-up for the recurrence rate and overall survival time after diagnosis. There was no significant difference in clinical variables between EG and CG. During treatment, dogs of EG showed a significant reduction in erythrocyte, hemoglobin, and hematocrit values between T0 and T1, T2, T3, and T4 (P < 0.001). Comparatively, the CG showed significant reduction in hemoglobin (P = 0.02) and total leucocytes (P = 0.001) values in the same period. Despite these findings, these hematological parameters did not exceed the lower limit for the species in both groups. There was a higher-grade neutropenia one week after the first VBL application (T2) in both groups, with no statistical difference in neutrophil counts at T2 or during the whole treatment. There were discrete and self-limited episodes of anorexia, vomiting, and diarrhea in both groups. After chemotherapy, dogs in EG showed a significantly lower rate of recurrence than dogs in CG (P = 0.02). There was no significant difference in the overall survival time between groups. Discussion: The absence of significant differences in clinical variables (e.g. sex, age, histological grading, and tumor location) between EG and CG suggests that the groups may be similar regarding these parameters. All dogs included in this study had a recommendation for MCT post-operative chemotherapy treatment. VBL action is non-selective and anemia is not a commonly described adverse effect associated with its administration. Despite that, EG dogs exhibited a reduction in erythrocytes, hematocrit, and hemoglobin, and CG dogs in hemoglobin throughout T0 to T4. The highest number of neutropenia episodes occurred during T2, after the first VBL application in both groups with a trend of stabilization after T2, which is compatible with findings described in the literature. Any dog of EG or CG had to interrupt the treatment due to hematological or gastrointestinal toxicity or died during treatment. The role of VBL dose intensity in outcome is still debatable for dogs with MCT, once it is a multifactorial disease with variable presentation. In this study, there was no difference in overall survival time after diagnosis between groups, and EG dogs treated with a higher VBL dose showed significantly less tumor recurrence than CG.